El reportaje como medio de sensibilización sobre el abandono de perros en la ciudad de Latacunga, sector La Estación - Pachi Sarabia, Ivette Verónica (2016)
The objective of this research is to raise public awareness through a very important genre in communication as in the story, where the reality of the dogs will be shown in abandonment of the city of Latacunga, especially in the sector Station, which creates inconvenience to passers circulating adjacent to these places. The project is based on theoretical foundations related to the development of a report, the aspects are also considered to reach the awareness of humanity. In the research methodology is descriptive research for problem analysis, the methods, deductive and field, applying the interview technique that allowed to establish the views of those involved in relation to the abandonment of dogs. The information gathered activists, authorities and veterinary professionals analyzed and interpreted respectively, with which the views of each was determined with the problem and taken into account in carrying out the report “Abandoned dogs”. The same is intended to raise awareness of the city of Latacunga regarding stray dogs, which seeks to inform the public about the situation in which these animals are already while generating a culture of aid and respect for animals.